A phenomenological interpretation of Taqwa as an instrument of character building - Busari, Saheed Abdullahi (University of Lagos Press and Bookshop Ltd, 2022)
Taqwā or Piety is the act of establishing relationship with Allah through unconditional obedience. Taqwa and its derivatives are extensively mentioned in the Quran with several semantics significations including its depiction as righteousness, piety, self-restrain and justice. The Quran presents Taqwa as a mechanism for accessing divine guidance and adhering to it wholeheartedly. This paper explores the utilities of Taqwa in the light of Quranic submission that "whoever fears Allah", He will make for him a way out". The study employs an interpretative phenomenological approach in presenting the classical and contemporary interpretation of this verse as well as the lived experiences of prophets and outstanding scholars. This study found that Taqwa is an instrument for imbibing and exhibiting praiseworthy conduct. The strict implementation of the dictates of Taqwa is a precondition for achieving ultimate success. The study suggests the development of a Tqawa framework for social reconstruction in the school and family systems as well as the wider society.